Influence of themo-mechanical treatments and microstructural state on the fatigue behaviour of a weald seam: case of API X60 steel (Fracture and Structural Integrity, 2021)
The aim of this work is the study of the fatigue behaviour of API X60 steel and the influence of thermal and mechanical treatments. The evaluation of the integrity and safety of welded structures dictates the approach taken in this research. The microstructural observations on the different zones of the weld seam indicates that the variation of heterogeneous structure is a progressive destruction of the strips of lamination which cause a new phase leading to a drop in the mechanical properties requiring treatment after welding. The fatigue cracking rate diverges beyond the threshold of DK, but no deviation of the crack from its propagation axis was noticed, which confirms the correct choice of filler metal over that of the base metal with an overmatching M = 1.1, and the treatments applied to the structure. This fatigue cracking rate transversal to the welding direction initially presents an aspect similar to that of BM but registers a delay as soon as the crack tip enters the second zone (HAZ) then it progresses rapidly. This evolution is characterized by a disturbance due to the repeated change of microstructure.
Keywords: Fatigue crack; Thermal-mechanical treatment; microstructure of welded joints; crack propagation; mechanical properties of API X60 steel; chemical composition.